2011
DOI: 10.1007/s12975-011-0080-6
|View full text |Cite
|
Sign up to set email alerts
|

Low-Power 2-MHz Pulsed-Wave Transcranial Ultrasound Reduces Ischemic Brain Damage in Rats

Abstract: It is largely unknown whether prolonged insonation with ultrasound impacts the ischemic brain tissue by itself. Our goal was to evaluate safety and the effect of high-frequency ultrasound on infarct volume in rats. Thirty-two Long-Evans rats with permanent middle cerebral and carotid artery occlusions received either 2-MHz ultrasound at two levels of insonation power (128 or 10 mW) or no ultrasound (controls). We measured cerebral hemorrhage, indirect and direct infarct volume as well as edema volume at 24 h. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The rationale why we decided to analyze patients with severe stroke severity is based on the fact that these patients most commonly (>80%) have an underlying proximal major occlusion (3,4), and hence, only modest benefits with IV tPA therapy (5). Also, even though the continuous exposure of cerebral ischemic tissues to ultrasound seems to have additional effects (21), it benefits patients mostly by improving early recanalization of a large thrombo-embolic occlusion. Rapid arterial recanalization and restoration of perfusion belong to the most important independent predictors of good functional outcome after AIS (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The rationale why we decided to analyze patients with severe stroke severity is based on the fact that these patients most commonly (>80%) have an underlying proximal major occlusion (3,4), and hence, only modest benefits with IV tPA therapy (5). Also, even though the continuous exposure of cerebral ischemic tissues to ultrasound seems to have additional effects (21), it benefits patients mostly by improving early recanalization of a large thrombo-embolic occlusion. Rapid arterial recanalization and restoration of perfusion belong to the most important independent predictors of good functional outcome after AIS (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…We know of only two publications relevant to the cerebral vasculature. In rats, Alexandrov and colleagues [ 65 ] reported significant reductions in the volume of edematous and ischemic brain with application of a commercially available TCD with a 2.0-MHz carrier frequency, 10-mW acoustic power, and 5-KHz pulse repetition frequency. They observed significant reductions in the volume of ischemic and edematous brain (75 vs. 22.5 mm 3 ; 12.7 vs. 1.56 mm 3 , respectively) [ 65 ].…”
Section: Reviewmentioning
confidence: 99%
“…In rats, Alexandrov and colleagues [ 65 ] reported significant reductions in the volume of edematous and ischemic brain with application of a commercially available TCD with a 2.0-MHz carrier frequency, 10-mW acoustic power, and 5-KHz pulse repetition frequency. They observed significant reductions in the volume of ischemic and edematous brain (75 vs. 22.5 mm 3 ; 12.7 vs. 1.56 mm 3 , respectively) [ 65 ]. Given the unlikely occurrence of cavitation in the brain with these parameters [ 63 , 64 ], we hypothesize this may have occurred through US-mediated enhancement of collateral flow in the volume of tissue surrounding the region of ischemic damage, due to local US-induced vasodilation of collateral blood vessels via stimulation of NO pathways as discussed, or production of enhanced flow via acoustic streaming.…”
Section: Reviewmentioning
confidence: 99%
“…The CLOTBUST-ER trial was based on a previous Phase II trial (CLOTBUST) which showed an improved recanalization rate if alteplase was combined with continuous transcranial ultrasound monitoring as compared to alteplase alone [52]. Different mechanisms of action of ultrasound have been considered including better penetration of thrombolytic agents into the clot due to induction of 'microstreaming' in the residual flow around the thrombus or improvement of the microcirculation leading to decreased infarct volume [106].…”
Section: Enhanced Intravenous Thrombolysis In Acute Ischaemic Strokementioning
confidence: 99%